Seasonal Zooplankton Distribution and Species Composition in the Eastern Sea of Marmara - Melek İşinibilir; Ezgi Türkeri (Aquatic Sciences and Engineering)
Seasonal changes in the composition and abundance of zooplankton and their responses to environmental changes were investigated at 30 stations in the upper layer and 13 stations in the lower layer (in February, May, July, and December) of the Eastern Marmara Sea in 2016. A total of 44 species/groups (including jellyfish species) were documented in the study area, with 39 identified in the upper layer water and 31 in the lower layer water. The abundances of zooplankton ranged from 29 to 2822 ind.m−3 in the upper layer and from 6 to 2283 ind.m−3 in the lower layer. Acartia clausi, Paracalanus parvus, Penilia avirostris, and Oithona similis were the dominant species in summer and autumn, whereas Calanus euxinus, Pseudocalanus elongates, Oithona nana, Oithona davisae and Pleopis polyphemoides were the dominant species in winter and spring. Aetideus spp., Clausocalanus spp., Ctenocalanus vanus, Oncaea minuta, Isopoda, and Siphonophora were observed only in bottom-layer waters. M. lucens and O. davisae were recorded only in the upper layer in December. In conclusion, our results suggest that zooplankton communities and some species are favorable indicators of the marine environment of the Sea of Marmara.